2014
DOI: 10.1155/2014/704619
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chlorella and Its Hot Water Extract Supplementation on Quality of Life in Patients with Breast Cancer

Abstract: A self-control, randomized, and open-label clinical trial was performed to test the effects of the unicellular green algae Chlorella and hot water extract supplementation on quality of life (QOL) in patients with breast cancer. Forty-five female patients with breast cancer who were living at home and not hospitalized were randomly assigned to 3 groups receiving vitamin mix tablet (control), Chlorella granules (test food-1), or Chlorella extract drink (test food-2) daily for one month. The Functional Assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
1
19
0
3
Order By: Relevance
“…Many other reviews reached similar conclusions, reporting positive, moderate effect sizes of mind-body interventions (MBIs) on anxiety and distress in cancer. 174,175,316 Anemia LCS101 combination botanical, 200 RG-CMH combination botanical, 201 shenqi fuzheng injection 202 Anxiety/stress reduction Art therapy, 203,204 comprehensive coping strategy, 205 electrical nerve stimulation, 206 Pain Comprehensive coping strategy, 205 stress management, 36 vitamin D2, 254 electrical nerve stimulation, 206 cognitive and behavioral therapy, 255 hypnosis, 256 massage, 88 myofascial release, 209 reflexology 139,212 Quality of life Acupressure, 216 Biofield Healing 225 calendula cream, 257 cannabis, 258 chlorella extract, 259 CoQ10, 226 curcuminoids, 260 electrical nerve stimulation, 206 electrotherapy, 245 flaxseed, 261 Ganoderma lucidum, 227 gingko forte, 246 guided imagery, 262 Radiation therapy-induced toxicity outcomes Adlay bran extract, 274 alpha ointment with henna, 275 Aquaphor-Biafine-Radiacare, 276b boswellia cream, 277 calendula cream, 257,278 chamomile, 279 curcumin, 280 glutamine, 281 homeopathic pills, 282 honey, 283,284 hydration,…”
Section: Meditation (A Grade)mentioning
confidence: 99%
“…Many other reviews reached similar conclusions, reporting positive, moderate effect sizes of mind-body interventions (MBIs) on anxiety and distress in cancer. 174,175,316 Anemia LCS101 combination botanical, 200 RG-CMH combination botanical, 201 shenqi fuzheng injection 202 Anxiety/stress reduction Art therapy, 203,204 comprehensive coping strategy, 205 electrical nerve stimulation, 206 Pain Comprehensive coping strategy, 205 stress management, 36 vitamin D2, 254 electrical nerve stimulation, 206 cognitive and behavioral therapy, 255 hypnosis, 256 massage, 88 myofascial release, 209 reflexology 139,212 Quality of life Acupressure, 216 Biofield Healing 225 calendula cream, 257 cannabis, 258 chlorella extract, 259 CoQ10, 226 curcuminoids, 260 electrical nerve stimulation, 206 electrotherapy, 245 flaxseed, 261 Ganoderma lucidum, 227 gingko forte, 246 guided imagery, 262 Radiation therapy-induced toxicity outcomes Adlay bran extract, 274 alpha ointment with henna, 275 Aquaphor-Biafine-Radiacare, 276b boswellia cream, 277 calendula cream, 257,278 chamomile, 279 curcumin, 280 glutamine, 281 homeopathic pills, 282 honey, 283,284 hydration,…”
Section: Meditation (A Grade)mentioning
confidence: 99%
“…1). Review studies published within the last 6 years (2011-2017) were conducted in the following countries: Brazil [11,17], the United States [12,18,19], Japan [20,21], and Malaysia [22]. All 932 women who were diagnosed with breast cancer or were cancer survivors were included in the review.…”
Section: Resultsmentioning
confidence: 99%
“…The sample size of the studies ranged from 30 to 409. One study used two intervention groups (IGs) and one control group (CG) [21], and one study did not report loss to follow-up [22]. Meanwhile, other studies reported from one to 97 patients lost to follow-up [12,19].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations